Cost optimisation approach for cloud-based smart grid data management. (2016) - Raju, Dasari Naga; Saritha, V.
The smart grid is an advanced power grid with efficient two-way communication of power and data. Due to the modular nature of network and users, the data storage and processing were required. Cloud computing is one of the efficient technology for storing and managing such data in the real world. To solve such data management issues, we proposed a cloud-based smart grid data management (CSGDM) model and an optimisation algorithm to resolve the challenges of such environment. The proposed algorithm deals with the grid utilisation and power usage cost calculation with an optimisation mechanism for cost function to minimise the data storage prices.